Lipophilic cationic drugs increase the permeability of lysosomal membranes in a cell culture system - Kornhuber, Johannes; Henkel, Andreas W.; Groemer, Teja W.; Städtler, Sven; Welzel, Oliver; Tripal, Philipp; Rotter, Andrea; Bleich, Stefan; Trapp, Stefan (Journal of Cellular Physiology, 2010)
Lysosomes accumulate many drugs several fold higher compared to their extracellular concentration. This mechanism is believed to be responsible for many pharmacological effects. So far, uptake and release kinetics are largely unknown and interactions between concomitantly administered drugs often provoke mutual interference. In this study, we addressed these questions in a cell culture model. The molecular mechanism for lysosomal uptake kinetics was analyzed by live cell fluorescence microscopy in SY5Y cells using four drugs (amantadine, amitriptyline, cinnarizine, flavoxate) with different physicochemical properties. Drugs with higher lipophilicity accumulated more extensively within lysosomes, whereas a higher pKa value was associated with a more rapid uptake. The drug-induced displacement of LysoTracker was neither caused by elevation of intra-lysosomal pH, nor by increased lysosomal volume. We extended our previously developed numerical single cell model by introducing a dynamic feedback mechanism. The empirical data were in good agreement with the results obtained from the numerical model. The experimental data and results from the numerical model lead to the conclusion that intra-lysosomal accumulation of lipophilic xenobiotics enhances lysosomal membrane permeability. Manipulation of lysosomal membrane permeability might be useful to overcome, for example, multi-drug resistance by altering subcellular drug distribution. © 2010 Wiley-Liss, Inc.
Created from Fastlane, Scopus look-up